2021
DOI: 10.1080/02770903.2021.1922915
|View full text |Cite
|
Sign up to set email alerts
|

Usage of long-acting muscarinic antagonists and biologics as add-on therapy for patients in the United States with moderate-to-severe asthma

Abstract: Objective: Many asthma patients remain uncontrolled on inhaled corticosteroids (ICS) and long-acting beta agonists (LABAs), but guidance for selecting add-on therapies, including long-acting muscarinic antagonists (LAMAs) or biologics, is limited. We describe how prescribing practices for add-on LAMA and biologic therapy have changed with increased treatment options and revised treatment guidelines. We further identify differences in treatment initiation and discontinuation rates by patient characteristics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Finally, the impact of early refills was assessed in 46 out of 116 studies (exclusion of initiation studies and implementation methods based on all days supplied as oversupply is automatically included). In general, for patients who refilled Time between end of one prescription and the start of a subsequent one Treatment gap of >X days between the end of one prescription and the start of the subsequent one [16,30,37,41,43,51,58,59,62,63,79,81,109,112,126,128,147,149,151,158,173,176] Treatment gap of >X days between the end of one prescription (prescription end corrected for early refills) and the start of the subsequent one [47,60,80] Treatment gap of >X days between the end of one prescription (prescription end corrected for inpatient stays) and the start of the subsequent one [38,91] Treatment gap of >X days between the end of one prescription (prescription end corrected for early refills and inpatient stays) and the start of the subsequent one [98,119] Treatment gap of >X days (value of X adapted for inpatient stays) between the end of one prescription and the start of the subsequent one [85] Treatment gap of >X days between the end of one prescription and the start of the subsequent one and no re-initiation during the subsequent period [154,155]…”
Section: Adherence Measurement Methodsmentioning
confidence: 99%
“…Finally, the impact of early refills was assessed in 46 out of 116 studies (exclusion of initiation studies and implementation methods based on all days supplied as oversupply is automatically included). In general, for patients who refilled Time between end of one prescription and the start of a subsequent one Treatment gap of >X days between the end of one prescription and the start of the subsequent one [16,30,37,41,43,51,58,59,62,63,79,81,109,112,126,128,147,149,151,158,173,176] Treatment gap of >X days between the end of one prescription (prescription end corrected for early refills) and the start of the subsequent one [47,60,80] Treatment gap of >X days between the end of one prescription (prescription end corrected for inpatient stays) and the start of the subsequent one [38,91] Treatment gap of >X days between the end of one prescription (prescription end corrected for early refills and inpatient stays) and the start of the subsequent one [98,119] Treatment gap of >X days (value of X adapted for inpatient stays) between the end of one prescription and the start of the subsequent one [85] Treatment gap of >X days between the end of one prescription and the start of the subsequent one and no re-initiation during the subsequent period [154,155]…”
Section: Adherence Measurement Methodsmentioning
confidence: 99%
“…Claims data include patient demographics, diagnosis and procedure codes, hospitalizations and office visits, and the presence of each of the 27 chronic conditions defined by the Chronic Conditions Warehouse 32 . Patients were included if they were 18 or older, were alive at the end of 2015, had at least 1 visit to a provider in one of our practices during the year, and had 2 or more claims for either coronary artery disease (CAD) or diabetes using International Classification of Disease (ICD-9 and ICD-10) codes 33–35 . These conditions were chosen as they are 2 of the most common chronic diseases affecting Medicare-enrolled patients.…”
Section: Methodsmentioning
confidence: 99%
“…32 Patients were included if they were 18 or older, were alive at the end of 2015, had at least 1 visit to a provider in one of our practices during the year, and had 2 or more claims for either coronary artery disease (CAD) or diabetes using International Classification of Disease (ICD-9 and ICD-10) codes. [33][34][35] These conditions were chosen as they are 2 of the most common chronic diseases affecting Medicare-enrolled patients.…”
Section: Patient Samplementioning
confidence: 99%
“…1,2 The addition of a LAMA to ICS/LABA maintenance therapy has been shown to improve lung function and symptoms and reduce exacerbation rates in patients with uncontrolled asthma; furthermore, the addition of LAMA is likely to incur substantially lower costs compared with escalating to biologic therapy. [16][17][18][19][20] Until recently, the addition of a LAMA to ICS/LABA therapy (ie, triple therapy) for asthma maintenance was only available in the form of multiple-inhaler triple therapy (MITT), usually with different devices or differing dosing regimens. 2 Real-world observational studies in the United States and Japan reported low adherence to, and persistence with MITT among patients with asthma requiring triple therapy.…”
mentioning
confidence: 99%